THE ROLE OF THE STRICT CIVIL LIABILITY IN CONSUMER PROTECTION AND THE NEED FOR ITS APPLICATION IN THE ADVERTISING FIELD (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In this paper, we discuss the role of strict liability in consumer protection, in terms of reviewing the basis of substantive responsibility and reviewing many of its applications in this field. To extend their scope to civil liability in advertising.Accordingly, we will show the contemporary legislative direction to extend the strict liability in many areas with a view to protecting members of society from harm that may affect them, by recognizing their right to compensation without requiring the fault of the defendant, with the creation of financial resources allocated for this purpose, such as compensation For damages associated with medical treatment, compensation for damage caused by defective products, and the responsibility of the air carrier for the safety of passengers.Thus, we will focus on TV channels ads as well as new media technologies advertisement methods and the responsibilities of adviser or provider and how regulations could adapt to these new innovated ads techniques.The research has two parts, first part related to the law perspective point of view, the second one is related to the media advertisement field.